Human Rights and Fundamental Freedoms as the Basis of the Finnish Constitution - K. Nuotio (Теоретическая и прикладная юриспруденция)
In the article, the author describes the history of the formation of constitutional legislation in Finland and, in particular, notes the key events and participants in the process of constitutionalism in the country. The author describes the Finnish arrangement for monitoring that the adopted laws comply with the Finnish constitution and its provisions of fundamental rights as well as the human rights obligations of Finland. Of particular importance in the article is the description of the development of the institution of fundamental human rights and freedoms, their form of consolidation in the legislation, as well as the shrinking role of customary law. The author emphasizes the important role of the provisions of the Constitution not only in guaranteeing the realization of rights and freedoms, but also in providing guidance for the subsequent development of legislative regulation on various fields of law, including the rights and duties relating to providing of a healthy environment.